Pengaruh Kepuasan Kerja dan Gaya Kepemimpinan terhadap Kinerja Karyawan di PT. Samudera Gemilang Nusantara - Saputra, Insan Kamil (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the effect of job satisfaction and leadership style on employee performance at PT. Samudera Gemilang Nusantara. The approach used is an explanatory study with an online survey method. Data collection was carried out through a questionnaire with a five-point Likert scale, and respondents were selected using a simple random sampling technique. A total of 80 employees participated in this study. The results of the analysis show that job satisfaction has a positive and significant effect on employee performance. This finding confirms the results of previous studies which state that job satisfaction is an important factor in improving performance. In addition, leadership style has also been shown to have a significant effect on performance, where leaders who are able to provide clear direction, support, and create a positive work environment can encourage employee productivity. This study provides an empirical contribution in strengthening the understanding of the role of job satisfaction and leadership style in improving employee performance in an organizational environment.